Regulation of antioxidant enzyme activities in male and female rat macrophages by sex steroids - Azevedo, R.B. (2001)
Human and animal immune functions present sex dimorphism that seems to be mainly regulated by sex hormones. In the present study, the activities of the antioxidant enzymes total superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) were measured in intraperitoneal resident macrophages from adult male and female rats. In addition to comparing males and females, we also examined the regulation of these enzyme activities in macrophages by sex steroids. GSH-Px activity did not differ between male and female macrophages. However, both total SOD and CAT activities were markedly higher in females than in males (83 and 180%). Removal of the gonads in both males and females (comparison between castrated groups) increased the difference in SOD activity from 83 to 138% and reduced the difference in CAT activity from 180 to 86%. Castration and testosterone administration did not significantly modify the activities of the antioxidant enzymes in male macrophages. Ovariectomy did not affect SOD or GSH-Px activity but markedly reduced (48%) CAT activity. This latter change was fully reversed by estrogen administration, whereas progesterone had a smaller effect. These results led us to conclude that differences in the SOD and CAT activities may partially explain some of the differences in immune function reported for males and females. Also, estrogen is a potent regulator of CAT in macrophages and therefore this enzyme activity in macrophages may vary considerably during the menstrual cycle.